Age-related changes in cervical sagittal alignment: based on 625 Chinese asymptomatic subjects - Wang, Zheng; Liu, Xu; Hu, Xinli; Cui, Peng; Wang, Wei; Kong, Chao; Lu, Shibao (European spine journal, 2023)
Purpose This work aimed to provide a comprehensive description of cervical alignment including cranial arch and caudal arch according to age, thus offering a reference database for cervical deformity treatment. Methods Total 150 males and 475 females aged at 48–88 were enrolled from August 2021 to May 2022. Radiographic parameters were measured, including Occipito-C2 angle (O-C2), C2-7 angle (C2-7), cranial arch, caudal arch, T1-slope (T1s), and C2-7 sagittal vertical axis (C2-7 SVA). Pearson correlation coefficient was employed in analyzing associations among sagittal parameters and between age and each parameter. Five groups were set according to different age stages, namely group with age 40–59 ( N = 77), group with age 60–64 ( N = 189), group with age 65–69 ( N = 214), group with age 70–74 ( N = 97), and group with age exceeding 75 ( N = 48). An analysis of variance (ANOVA) test was applied to compare multi-sets of cervical sagittal parameters (CSPs). Chi-square test or Fisher’s exact test was used in assessing the relationships of various cervical alignment patterns with age groups. Results T1s exhibited the strongest correlation with C2-7 ( r = 0.655) and caudal arch ( r = 0.561), and moderately correlated with cranial arch ( r = 0.355). The positive correlations between age and C2-7 angle ( r = 0.189, P < 0.001), cranial arch ( r = 0.150, P < 0.001), caudal arch ( r = 0.112, P = 0.005), T1s ( r = 0.250, P < 0.001), as well as C2-7 SVA ( r = 0.090, P = 0.024) were observed. Moreover, two progressive growths of C2-7 were shown after 60–64 and 70–74 years old, respectively. Thereof, cranial arch increased greatly after the age of 60–64, followed by a relative stability in the degeneration. The notable growth of caudal arch was observed after the age of 70–74, and the growth remained stable when exceeding the age of 75. The difference between cervical alignment patterns and age groups was obvious (Fisher’s exact test P < 0.001). Conclusion This work explored in detail the normal reference values of cervical sagittal alignment including cranial arch and caudal arch under different age groups. Age-related changes in cervical alignment depended on the increase in the cranial and caudal arches in different proportions with age.